Clinical features of patients who had two COVID‐19 episodes: a European multicentre case series. (10th March 2021) - Lechien, J. R.; Chiesa‐Estomba, C. M.; Radulesco, T.; Michel, J.; Vaira, L. A.; Le Bon, S. D.; Horoi, M.; Falanga, C.; Barillari, M. R.; Hans, S.; Tucciarone, M.; Saussez, S.
Abstract: Objective: To investigate the clinical features of patients who had two demonstrated coronavirus disease 2019 (COVID‐19) episodes. Methods: Data of patients with both COVID‐19 episodes were recruited from 22 March to 27 December 2020. The following outcomes were studied: epidemiological, comorbidities, prevalence and severity of general and otolaryngological symptom, olfactory, aroma, and gustatory dysfunctions. A comparison between first and second episodes was performed. Results: Forty‐five patients reported having two confirmed COVID‐19 episodes. The majority of patients had mild infections in both episodes. The second clinical episode was significantly similar to the first. The symptom duration of the second episode was shorter than the first. The occurrence of loss of smell was unpredictable from the first to the second episode. Conclusion: The recurrence of COVID‐19 symptoms is associated with a similar clinical picture than the first episode in patients with initial mild‐to‐moderate COVID episode. The pathophysiological mechanisms underlying the development of second episode remain uncertain and may involve either true reinfection or virus reactivation from sanctuaries.